Preparation method of aqueous positive electrode slurry for sodium ion battery, pole piece and sodium ion battery
In the preparation process of sodium ion battery positive electrode slurry, the aqueous positive electrode slurry is used, sodium layered oxide positive electrode material and polyanionic sodium ion positive electrode material are used, and graphite conductive agent and water-based binder are combined, and acetyl halide short-chain acyl organic matter is added as pH adjustment additives. The problems of inconsistent adhesiveness, poor process stability, large safety hazards and high environmental pressure in the preparation process of positive electrode slurry in the prior art are solved, and the effects of low cost, excellent electrochemical performance, good stability and simple process are achieved.
Patent Information
- Application Number
- CN202210637296.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-07
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-06-07
AI Technical Summary
In the preparation process of existing sodium ion battery positive electrode slurry, there are problems such as inconsistent adhesiveness, poor process stability, large safety hazards and high environmental pressure, especially the problems of high cost, strict environmental requirements and high environmental pressure in polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (NMP) systems.
The preparation method of the aqueous positive electrode slurry is adopted, through the ingredients, mixing and parameter adjustment steps, sodium layered oxide positive electrode material, polyanionic sodium ion positive electrode material, graphite conductive agent, sodium carboxymethylcellulose as thickener, and styrene butadiene rubber as water-based binder, and acetyl halide short-chain acyl organic matter as pH adjustment additives are added to prepare a sodium ion battery positive electrode slurry with excellent electrochemical properties.
The positive electrode slurry of sodium ion battery with low cost, excellent electrochemical performance, good stability and simple process is realized, which avoids cumbersome operations of the oily system, reduces the amount of binder, improves the uniformity and peeling force of the electrode, and simplifies process operation.
Smart Images

Figure SMS_1 
Figure SMS_4 
Figure SMS_6
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a method for preparing aqueous positive electrode slurry for sodium ion batteries, a positive electrode sheet and a sodium ion battery. Background Art
[0002] Research on sodium-ion batteries and lithium-ion batteries started almost at the same time in the 1970s, and the latter has been widely used in various fields of the national economy. With the advent of the "carbon peak and carbon neutrality" era, the shortcomings of lithium-ion batteries due to resources, costs and safety are becoming increasingly apparent, making sodium-ion batteries a necessary supplement to lithium-ion batteries.
[0003] The process route of sodium-ion batteries is consistent with that of lithium-ion batteries, and the manufacturing process and equipment can follow the latter. However, in the preparation process of positive electrode slurry, lithium-ion batteries generally use polyvinylidene fluoride (PVDF) as a binder and N-methylpyrrolidone (NMP) as a solvent. The preparation process of the positive electrode slurry is an oily system preparation process.
[0004] Polyvinylidene fluoride (PVDF) as an adhesive needs to be used with N-methylpyrrolidone (NMP) as a solvent. The process is mature and the performance is good, but there are still the following problems:
[0005] 1. PVDF has many commercial specifications according to different molecular weights and functional groups. Low molecular weight PVDF has good uniformity after dissolution, but the amount added is large. High molecular weight PVDF has poor uniformity after dissolution with a small amount of addition, resulting in inconsistent local adhesion of the electrode. This is one of the reasons for the poor batch consistency of lithium-ion batteries.
[0006] 2. The positive electrode active material generally contains residual alkali (Li2CO3, Na2CO3) on the surface during the preparation process. In a single PVDF molecular chain, the connected H and F atoms are easily removed at the same time in an alkaline environment to form HF, which decomposes the binder, called alkaline hydrolysis, and the bonding effect decreases; more seriously, the H and F atoms in two PVDF molecular chains are removed in an alkaline environment to generate HF, generating CC single bonds, causing the molecular chains to aggregate into a "jelly-like" state. There are generally two solutions at present: First, add weak acid to neutralize the alkalinity during the pulping process, such as CN201710414118.2, but the amount of addition is difficult to accurately control, and the residual weak acid may react with the electrolyte and continue to deteriorate the battery performance. If the amount of residual alkali in the active material is accurately measured to determine the amount of weak acid to be added, this is not easy to achieve quickly at the production site; second, add an expensive dehumidification system to meet the low humidity requirements of the production site. The above two methods are often used in combination.
[0007] 3. The solvent NMP has a pungent odor and a flash point of 86°C. It can explode when the volume ratio in the air is 1.3~9.5%. There are certain safety hazards in the storage, transportation and battery production process. Finally, a condensation recovery system needs to be added to meet environmental protection requirements.
[0008] Due to the poor process stability of the PVDF binder system, the low dew point requirement in the production environment, the great environmental pressure, and the high price, directly applying PVDF and NMP to the preparation process of the positive electrode slurry of the sodium ion battery does not have direct mobility. Summary of the invention
[0009] The purpose of the present invention is to provide a method for preparing an aqueous positive electrode slurry for a sodium ion battery, a positive electrode sheet and a sodium ion battery, which have the characteristics of low cost, excellent electrochemical performance, good stability and simple process.
[0010] The present invention can be implemented by the following technical solutions:
[0011] The present invention discloses a method for preparing an aqueous positive electrode slurry for a sodium ion battery, comprising the following steps:
[0012] S1. Batching: Weigh the positive electrode active material, conductive agent, thickener, aqueous binder, and pH adjusting additive according to the mass ratio of 92-97: 1.0-3.0: 1.0-2.0: 2.0-5.0: 0.1-1.0 to complete the material batching;
[0013] S2. Mixing: Using deionized water as solvent, dissolving thickener to obtain thickener mother liquor, adding conductive agent to thickener mother liquor and stirring for 2-4 hours, then adding positive electrode active material and stirring and dispersing, then adding binder and deionized water, and vacuum stirring and degassing to obtain aqueous slurry;
[0014] S3, parameter adjustment: measuring the pH value of the aqueous slurry obtained in step S2, and adding a pH adjustment additive to adjust the pH value of the aqueous slurry to between 7 and 8, to obtain an aqueous slurry to be coated;
[0015] The positive electrode active material is a sodium layered oxide positive electrode material or a polyanion sodium ion positive electrode material;
[0016] The pH adjusting additives are acetyl halide short-chain acyl organic matter and adipoyl halide short-chain acyl organic matter;
[0017] The structural formula of acetyl halide short-chain acyl organic compound is:
[0018]
[0019] The structural formula of adipic acid halide short-chain acyl organic compound is:
[0020] ;
[0021] In the above structural formula, X represents F, Cl or Br, and R represents an alkyl group.
[0022] Furthermore, the conductive agent is a graphite conductive agent, a carbon black conductive agent, a VGCF conductive agent, or a CNT conductive agent; the conductive agent is added in the form of powder or conductive slurry.
[0023] Furthermore, the thickener is sodium carboxymethyl cellulose, acrylonitrile multipolymer, polyacrylic acid, sodium polyacrylate.
[0024] Furthermore, the water-based binder is one or a mixture of two or more of styrene-butadiene rubber, acrylonitrile multipolymer, polyacrylic acid, and sodium polyacrylate.
[0025] Furthermore, the positive electrode active material is an oxide positive electrode material or a polyanion sodium ion material; the oxide positive electrode material is Na 0.4-0.7 M x Mn 1-x O2, wherein M is one or more of Mn, Fe, Co, Ni, Cu, Zn, Ca or Mg; the polyanion sodium ion materials include NaFePO4, Na2FeP2O7, Na4Fe3(PO4)2(P2O7), Na3(VOPO4)2F, Na3V2(PO4)3, Na3V2(PO4)2F3, Na3Mn x Ti 1-x (PO4)3, NaTi2(PO4)3.
[0026] Furthermore, the obtained positive electrode active material is a doped modified active material or a carbon coated active material.
[0027] Furthermore, the aqueous slurry to be coated obtained in step S3 has a viscosity ranging from 600 to 10000 mPa·s.
[0028] Another aspect of the present invention is to protect a positive electrode plate for a sodium ion battery, which is prepared by coating the positive electrode slurry.
[0029] Another aspect of the present invention is to protect a sodium ion battery, which is prepared using the above-mentioned sodium ion battery positive electrode sheet.
[0030] The present invention provides a method for preparing a sodium ion battery aqueous positive electrode slurry, a positive electrode sheet and a sodium ion battery, which have the following beneficial effects:
[0031] First, the cost is low. Compared with the oily system of lithium-ion battery positive electrode material for slurry preparation, the use of water-based ingredients can effectively avoid various cumbersome operations in the slurry preparation process of the oily system, avoid excessive use of binder, and use cheap thickeners and water-based binder systems to effectively reduce costs;
[0032] Second, the electrochemical performance is excellent. The acetyl halide short-chain acyl organic matter and the adipic acid halide short-chain acyl organic matter added in step S3 are used as pH regulating additives, and undergo a hydrolysis reaction in water. The generated acidic substances react with the residual alkali on the surface of the active substance. The kinetic performance of the electrochemical reaction of the active substance after the reaction is better. Taking acetyl chloride as an example, the reaction process is as follows:
[0033] Moreover, the carbon chain length and the number of halogen atoms of the acyl halide can be flexible and varied, which has high flexibility and selectivity;
[0034] Third, the system has good stability. The hydrolyzed product is rich in the most polar carboxyl group (-COOH), a part of which can undergo esterification reaction with the thickener CMC to improve the stripping force of the electrode, which is conducive to long cycle life. The other part directly provides bonding ability and stabilizes the electrode structure.
[0035] Fourth, the process is simple. The surface residual alkali content of the positive electrode slurry prepared by the stable process route of the present invention is in a stable range, and its uniformity is good, which is conducive to determining the amount of acyl halide added, simplifying cumbersome operations, reducing workload, and having good process operability. DETAILED DESCRIPTION
[0036] In order to enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention is further described in detail below in conjunction with embodiments.
[0037] The present invention discloses a method for preparing an aqueous positive electrode slurry for a sodium ion battery, comprising the following steps:
[0038] S1. Batching: Weigh the positive electrode active material, conductive agent, thickener, aqueous binder, and pH adjusting additive according to the mass ratio of 92-97: 1.0-3.0: 1.0-2.0: 2.0-5.0: 0.1-1.0 to complete the material batching;
[0039] S2. Mixing: Using deionized water as solvent, dissolving thickener to obtain thickener mother liquor, adding conductive agent to thickener mother liquor and stirring for 2-4 hours, then adding positive electrode active material and stirring and dispersing, then adding binder and deionized water, and vacuum stirring and degassing to obtain aqueous slurry;
[0040] S3, parameter adjustment: measuring the pH value of the aqueous slurry obtained in step S2, and adding a pH adjustment additive to adjust the pH value of the aqueous slurry to between 7 and 8, to obtain an aqueous slurry to be coated;
[0041] The positive electrode active material is a sodium layered oxide positive electrode material or a polyanion sodium ion positive electrode material;
[0042] The pH adjusting additives are acetyl halide short-chain acyl organic matter and adipoyl halide short-chain acyl organic matter;
[0043] The structural formula of acetyl halide short-chain acyl organic compound is:
[0044]
[0045] The structural formula of adipic acid halide short-chain acyl organic compound is:
[0046] ;
[0047] In the above structural formula, X represents F, Cl or Br, and R represents an alkyl group.
[0048] Furthermore, the conductive agent is a graphite conductive agent, a carbon black conductive agent, a VGCF conductive agent, or a CNT conductive agent; the conductive agent is added in the form of powder or conductive slurry.
[0049] Furthermore, the thickener is sodium carboxymethyl cellulose, acrylonitrile multipolymer, polyacrylic acid, sodium polyacrylate.
[0050] Furthermore, the water-based binder is one or a mixture of two or more of styrene-butadiene rubber, acrylonitrile multipolymer, polyacrylic acid, and sodium polyacrylate.
[0051] In the present invention, when the thickener and the binder are both acrylonitrile multi-polymer, polyacrylic acid, and sodium polyacrylate, only one or more of them need to be added to simultaneously have the bonding effect of the mixed system, which effectively simplifies the batching and mixing process and simplifies the process operation. The characteristic group of polyacrylonitrile multi-polymer is the strongly polar cyano group (-CN), which is a strongly polar bond, and N contains a lone pair of electrons, which is easy to form a hydrogen bond and has a good bonding effect; similarly, polyacrylic acid and sodium polyacrylate both have a strongly polar carboxylate group (-COO-), which can have a strong bonding effect.
[0052] Regarding the bonding system of the present invention, taking the CMC and SBR system as an example, CMC has strongly polar hydroxyl groups (-OH) distributed on the long molecular chain. The hydroxyl groups have good hydrophilicity and can provide strong bonding performance; the SBR emulsion particles provide bonding force through condensation reactions with active material particles and collectors through functional groups, and its "point" bonding and CMC's "chain" bonding complement each other in function. The CMC+SBR binder system uses deionized water as the solvent, which avoids the flocculation of PVDF in the organic solvent system under alkaline conditions, ensures the batch stability of the slurry, and does not have the safety and environmental pressure of the organic solvent system. The structural formula of CMC is:
[0053]
[0054] The -COO-Na group in CMC and the free Na after ionization + It has the following effects: improving the electrode / electrode liquid interface performance; enhancing ionic conductivity and reducing charge transfer impedance; supplementing sodium to form a sodium-rich state and improving the initial efficiency of sodium-ion batteries.
[0055] Similarly, sodium polyacrylate, due to its sodium ions, also has the corresponding function of CMC and can achieve similar technical effects.
[0056] Furthermore, the positive electrode active material is an oxide positive electrode material or a polyanion sodium ion material. The oxide positive electrode material is Na 0.4-0.7 M x Mn 1-x O2, wherein M is one or more of Mn, Fe, Co, Ni, Cu, Zn, Ca or Mg; the polyanion sodium ion materials include NaFePO4, Na2FeP2O7, Na4Fe3(PO4)2(P2O7), Na3(VOPO4)2F, Na3V2(PO4)3, Na3V2(PO4)2F3, Na3Mn x Ti 1-x (PO4)3, NaTi2(PO4)3.
[0057] Furthermore, the obtained positive electrode active material is a doped modified active material or a carbon coated active material.
[0058] Furthermore, the aqueous slurry to be coated obtained in step S3 has a viscosity ranging from 600 to 10000 mPa·s.
[0059] Another aspect of the present invention is to protect a positive electrode plate for a sodium ion battery, which is prepared by coating the positive electrode slurry.
[0060] Another aspect of the present invention is to protect a sodium ion battery, which is prepared using the above-mentioned sodium ion battery positive electrode sheet.
[0061] Example 1
[0062] According to the above preparation steps, a sodium ion battery positive electrode slurry was prepared according to the following mass ratio: 2 parts of NaFePO4 / C9, 2.0 parts of KS-6 C45, 3.0 parts of CMC, 3.0 parts of SBR, 20-80 parts of DIW, and 0.1 parts of acetyl chloride.
[0063] Example 2
[0064] According to the above preparation steps, a sodium ion battery positive electrode slurry was prepared according to the following mass ratio: 4 parts of NaFePO4 / C9, 2.0 parts of KS-6 C45, 2.0 parts of CMC, 2.0 parts of SBR, 20-80 parts of DIW, and 0.5 parts of acetyl chloride.
[0065] Example 3
[0066] According to the above preparation steps, a sodium ion battery positive electrode slurry was prepared according to the following mass ratio: 6 parts of NaFePO4 / C9, 2.0 parts of KS-6 C45, 1.0 parts of CMC, 1.0 parts of SBR, 20-80 parts of DIW, and 1.0 parts of acetyl chloride.
[0067] Example 4
[0068] According to the above preparation steps, a sodium ion battery positive electrode slurry was prepared according to the following mass ratio: 92 parts of Na2FeP2O7 / C, 2.0 parts of KS-6 C45, 3.0 parts of CMC, 3.0 parts of SBR, 20-80 parts of DIW, and 0.1 parts of acetyl chloride.
[0069] Example 5
[0070] According to the above preparation steps, a sodium ion battery positive electrode slurry was prepared according to the following mass ratio: 94 parts of Na2FeP2O7 / C, 2.0 parts of KS-6 C45, 2.0 parts of CMC, 2.0 parts of SBR, 20-80 parts of DIW, and 0.5 parts of acetyl chloride.
[0071] Example 6
[0072] According to the above preparation steps, a sodium ion battery positive electrode slurry was prepared according to the following mass ratio: 96 parts of Na2FeP2O7 / C, 2.0 parts of KS-6 C45, 1.0 parts of CMC, 1.0 parts of SBR, 20-80 parts of DIW, and 1.0 parts of acetyl chloride.
[0073] Example 7
[0074] According to the above preparation steps, a sodium ion battery positive electrode slurry was prepared according to the following mass ratio: 92 parts of Na4Fe3(PO4)2(P2O7) / C, 2.0 parts of KS-6 C45, 3.0 parts of CMC, 3.0 parts of SBR, 20-80 parts of DIW, and 0.1 parts of acetyl chloride.
[0075] Example 8
[0076] According to the above preparation steps, the sodium ion battery positive electrode slurry was prepared according to the following mass ratio: 94 parts of Na4Fe3(PO4)2(P2O7) / C, 2.0 parts of KS-6 C45, 2.0 parts of CMC, 2.0 parts of SBR, 20-80 parts of DIW, and 0.5 parts of acetyl chloride.
[0077] Example 9
[0078] According to the above preparation steps, a sodium ion battery positive electrode slurry was prepared according to the following mass ratio: 96 parts of Na4Fe3(PO4)2(P2O7) / C, 2.0 parts of KS-6 C45, 1.0 parts of CMC, 1.0 parts of SBR, 20-80 parts of DIW, and 1.0 parts of acetyl chloride.
[0079] Example 10
[0080] According to the above preparation steps, a sodium ion battery positive electrode slurry was prepared according to the following mass ratio: 92 parts of Na3V2(PO4)3 / C, 2.0 parts of KS-6 C45, 3.0 parts of CMC, 3.0 parts of SBR, 20-80 parts of DIW, and 0.1 parts of acetyl chloride.
[0081] Embodiment 11
[0082] According to the above preparation steps, the sodium ion battery positive electrode slurry was prepared according to the following mass ratio: 94 parts of Na3V2(PO4)3 / C, 2.0 parts of KS-6 C45, 2.0 parts of CMC, 2.0 parts of SBR, 20-80 parts of DIW, and 0.5 parts of acetyl chloride.
[0083] Example 12
[0084] According to the above preparation steps, the sodium ion battery positive electrode slurry was prepared according to the following mass ratio: 96 parts of Na3V2(PO4)3 / C, 2.0 parts of KS-6 C45, 1.0 parts of CMC, 1.0 parts of SBR, 20-80 parts of DIW, and 1.0 parts of acetyl chloride.
[0085] Comparative Example 1
[0086] According to the preparation steps of the oily system in the prior art, the positive electrode slurry for sodium ion battery was prepared according to the following mass ratio: NaFePO4 96 parts, KS-6 C45 2.0 parts, PVDF 2.0 parts, NMP (20-80 parts)
[0087] The prepared water-based and oil-based slurries were placed in a beaker, and the viscosity of the slurries was measured to evaluate the coating performance of the slurries. The prepared water-based and oil-based slurries were coated on aluminum foil, and after drying, the peeling force was tested with a tape, and the peeling condition was observed and described by naked eyes.
[0088] The above test results are shown in Table 1:
[0089] Table 1 Test results of the aqueous slurry to be coated and the electrode sheet after coating
[0090]
[0091] Appropriate slurry viscosity is one of the prerequisites for stable coating. Coating experiments show that when the slurry viscosity is between 600 and 10000 mPa·s, transfer coating can be stably performed, and the process window is wide, which is conducive to stable operation of the production line. As shown in Table 1, the viscosity in the embodiments is in the range of 600 to 10000 mPa·s. It can be reasonably inferred that the extrusion coating process can also operate stably within this viscosity range.
[0092] The above embodiments are only specific embodiments of the present invention, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and these obvious replacement forms all belong to the protection scope of the present invention.
Claims
1. A method for preparing an aqueous positive electrode slurry for a sodium ion battery, characterized in that The following steps are involved: S1. Batching: Weigh the positive electrode active material, conductive agent, thickener, aqueous binder, and pH adjusting additive according to the mass ratio of 92-97: 1.0-3.0: 1.0-2.0: 2.0-5.0: 0.1-1.0 to complete the material batching; S2. Mixing: Using deionized water as solvent, dissolving thickener to obtain thickener mother liquor, adding conductive agent to thickener mother liquor and stirring for 2-4 hours, then adding positive electrode active material and stirring and dispersing, then adding binder and deionized water, and vacuum stirring and degassing to obtain aqueous slurry; S3, parameter adjustment: measuring the pH value of the aqueous slurry obtained in step S2, and adding a pH adjustment additive to adjust the pH value of the aqueous slurry to between 7 and 8, to obtain an aqueous slurry to be coated; The positive electrode active material is a sodium layered oxide positive electrode material or a polyanion sodium ion positive electrode material; The thickener is one or a mixture of two or more of sodium carboxymethyl cellulose, acrylonitrile multipolymer, polyacrylic acid, and sodium polyacrylate; The pH adjusting additive is an acetyl halide short-chain acyl organic compound or an adipoyl halide short-chain acyl organic compound; The structural formula of the acetyl halide short-chain acyl organic compound is: The structural formula of the adipic acid halide short-chain acyl organic compound is: ; In the above structural formula, X represents F, Cl or Br, and R represents an alkyl group.
2. The method for preparing an aqueous positive electrode slurry for a sodium ion battery according to claim 1, characterized in that: The conductive agent is a graphite conductive agent, a carbon black conductive agent, a VGCF conductive agent, or a CNT conductive agent; the conductive agent is added in the form of powder or conductive slurry.
3. The method for preparing an aqueous positive electrode slurry for a sodium ion battery according to claim 1, characterized in that: The aqueous binder is one or a mixture of two or more of acrylonitrile multi-polymer, polyacrylic acid, and sodium polyacrylate.
4. The method for preparing an aqueous positive electrode slurry for a sodium ion battery according to claim 1, characterized in that: The oxide positive electrode material is Na 0.4-0.7 M x Mn 1-x O2, wherein M is one or more of Mn, Fe, Co, Ni, Cu, Zn, Ca or Mg; the polyanion sodium ion materials include NaFePO4, Na2FeP2O7, Na4Fe3(PO4)2(P2O7), Na3(VOPO4)2F, Na3V2(PO4)3, Na3V2(PO4)2F3, Na3Mn x Ti 1-x (PO4)3, NaTi2(PO4)3.
5. The method for preparing an aqueous positive electrode slurry for a sodium ion battery according to claim 1, characterized in that: The obtained positive electrode active material is a doped modified active material or a carbon coated active material.
6. The method for preparing an aqueous positive electrode slurry for a sodium ion battery according to claim 1, characterized in that: The aqueous slurry to be coated obtained in step S3 has a viscosity ranging from 600 to 10000 mPa·s.
7. A positive electrode plate for a sodium ion battery, characterized in that: The positive electrode slurry is prepared by coating any one of claims 1 to 6.
8. A sodium ion battery, characterized in that: Prepared by the sodium ion battery positive electrode sheet according to claim 7.
Citation Information
Patent Citations
Preparation method of positive water slurry, positive pole piece of lithium battery and lithium battery
CN107275574A
Electrode thickener and preparation method thereof
CN112072112A